2018
DOI: 10.1016/j.jcv.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Change in viral bronchiolitis management in hospitals in the UK after the publication of NICE guideline

Abstract: Overall there were modest but important improvements in the reported management of bronchiolitis after the publication of the NICE guideline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Previous studies carried out in hospitalized bronchiolitis patients also showed an improvement in the use of medications after the publication of the guidelines. In England, a similar study investigated the improvement in clinical practice after the 2015 NICE guidelines [15] and found a decrease in the use of salbutamol (from 47 to 30%), 3HS (from 55 to 33%), corticosteroids (from 7 to 2%), and epinephrine (from 22 to 12%) [25]. Another study conducted in the United States after implementation of the 2006 AAP guidelines showed a reduction in the use of nebulized medications (from 64.6 to 58%) and corticosteroids (from 24.7 to 16.3%) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies carried out in hospitalized bronchiolitis patients also showed an improvement in the use of medications after the publication of the guidelines. In England, a similar study investigated the improvement in clinical practice after the 2015 NICE guidelines [15] and found a decrease in the use of salbutamol (from 47 to 30%), 3HS (from 55 to 33%), corticosteroids (from 7 to 2%), and epinephrine (from 22 to 12%) [25]. Another study conducted in the United States after implementation of the 2006 AAP guidelines showed a reduction in the use of nebulized medications (from 64.6 to 58%) and corticosteroids (from 24.7 to 16.3%) [26].…”
Section: Discussionmentioning
confidence: 99%
“…19 A national survey looking at management practices of bronchiolitis across the UK found that routine testing of hospitalized infants for respiratory viruses dropped from 72% prior to the NICE guideline publication to 44% after. 25…”
Section: Clinical Usefulness Of Respiratory Virus Testingmentioning
confidence: 99%
“…8 A national survey in the UK found that individual trusts use a variety of cohorting practices including cohorting infants with the same causative virus, cohorting those with RSV, cohorting all infants with a clinical diagnosis of bronchiolitis in cubicles and cohorting all infants with a clinical diagnosis of bronchiolitis together, regardless of the causative virus. 25 These practices did not change significantly with the publication of the NICE guidance in 2015. 25 The AAP guideline recommends decontamination of hands with alcohol-based gel before and after every patient contact when managing patients with RSV.…”
Section: Transmission Of Rsv and Preventing Nosocomial Infections In mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are likely variations in compliance with such guidelines, e.g. as shown in with bronchiolitis management [28].…”
Section: Introductionmentioning
confidence: 99%